Reversibility of Hyperglycemic States in Children with Obesity - Diagnostic Pitfalls in the Assessment of Glucose Metabolism in Children and Adolescents with Obesity - Anna Iwańska; Małgorzata Wójcik; Ewa Szczudlik; Anna Stępniewska; Jerzy B. Starzyk (Galenos Yayincilik, 2024)
INTRODUCTION: Disorders of glucose metabolism in children with obesity are less common than in adults. There is also evidence that they may be transient. The aims of this study were to determine the prevalences of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and type 2 diabetes mellitus (DM2) and its reversibility in pediatric patients with obesity and to define the factors determining the reversibility of prediabetes or progression to diabetes. METHODS: Retrospective analysis included of young patients with obesity. Patients presented and were treated between 2000-2022 at a single center. RESULTS: The study included 573 (316 girls; 55.15%) Caucasian patients with median body mass index (BMI) Z-score of 3.95 (range 2.0-9.9) and median age 13.9 (2.9-17.1) years old. OGTT results were normal in 90.8% (n=520) and signs of prediabetes occurred in 9.2% (n=53); IFG 17%, IGT 88.7%, DM 0%. Among those who underwent OGTT twice (n=53), impaired glucose regulation was present in 9.3% (n=5) (IFG 40%, IGT 80%, DM 0%) at baseline and in 14.8% subject (n=8) (IFG 25%, IGT 50%, DM 25%) at follow-up after lifestyle modification only. After 12-36 months of follow up, in those with a history of IGT, 60% reverted to normal glucose tolerance, while IFG and IGT persisted in 20% and 20%, respectively, and none progressed to DM. The risk factors for progression of glucose metabolism disorders were increase of BMI Z-score, higher insulin levels and elevated homeostatic model assessment-insulin resistance. DISCUSSION AND CONCLUSION: IFG and IGT are common in pediatric patients with obesity, while the progression to DM2 is rare. Disorders of glucose metabolism have reversible character.